Arthroscopic Rotator Cuff Repair With Superior Capsule Reconstruction for Irreparable Supraspinatus Tears - Mark T. Langhans MD, PhD; Aliya G. Feroe MD, MPH; Jonathan D. Barlow MD; Christopher L. Camp MD (SAGE Publishing, 2024)
Background: Irreparable rotator cuff tears represent approximately 12% of all presenting cuff tears, and multiple surgical techniques have been described for treatment, including allograft/bridge augmentation, debridement, partial repair, subacromial balloon, tendon transfer, and superior capsule reconstruction (SCR). SCR has demonstrated durable improvement in range of motion (ROM) and outcome scores at 2 and 5 years. Indications: Surgical indications for SCR include an irreparable tear of the supraspinatus and/or infraspinatus with a preserved or reparable subscapularis and preserved glenohumeral joint cartilage. Technique Description: Diagnostic arthroscopy is performed to identify and characterize the rotator cuff tear. Thorough debridement of the greater tuberosity is performed. Two all-suture FiberTak anchors are placed in the superior aspect of the glenoid. Two 2.6-mm FiberTak suture anchors are placed in the humeral head at the chondral margin. After measuring, the dermal allograft is cut to size with 15-mm overhang left on the far lateral edge. A 12-mm passport cannula is inserted laterally and the sutures from the glenoid and humeral head anchors are brought out through the cannula maintaining their position and orientation. The sutures are passed through the graft outside the cannula. The graft is introduced into the shoulder via the passport cannula with a back grasper. A cannula-in-cannula technique is used to tie the glenoid anchors first and then the medial row anchors. Two lateral row swivel lock anchors are used to complete a standard double row repair. Margin convergence is performed between the dermal allograft and remaining rotator cuff anterior and posterior. Postoperatively, patients are kept in a sling for 6 weeks, with no shoulder ROM. From weeks 6 to 12, patients discontinue sling and begin passive progression to active ROM. Strengthening is initiated at 12 weeks, and return-to-sport or work is at approximately 6 months. Results: Irreparable rotator cuff tears treated with arthroscopic rotator cuff repair and SCR show durable improvement in patient-reported outcomes at 2 and 5 years. Re-tear rates did not differ between athletes and non-athletes. Discussion/Conclusion: Arthroscopic rotator cuff repair with SCR is a durable and reliable surgical option for patients presenting with preserved glenohumeral joint and irreparable supraspinatus and/or infraspinatus tear. Patient Consent Disclosure Statement: The author(s) attests that consent has been obtained from any patient(s) appearing in this publication. If the individual may be identifiable, the author(s) has included a statement of release or other written form of approval from the patient(s) with this submission for publication.